Discrimination of von Willebrands Disease (VWD) Subtypes: Direct Comparison of von Willebrand Factor:Collagen Binding Assay (VWF:CBA) with Monoclonal Antibody (MAB) Based VWF-capture Systems - Favaloro, Emmanuel J.; Henniker, Anthony; Facey, David; Hertzberg, Mark (Thrombosis and Haemostasis, 2000)
Discrimination of von Willebrand’s Disease (VWD) subtypes is important since it influences management. Qualitative [ie Type 2A, 2B, 2M] defects exhibit von Willebrand factor (VWF) discordance and give high VWF:Ag to VWF:’activity’ ratios. Classically, VWF:’activity’ is assessed using the VWF:RCof assay. The VWF:CBA is an ELISAbased VWF-functional adhesive assay which has consistently proved to be superior to VWF:RCof. A commercially available monoclonal antibody (MAB) based ELISA assay system claimed to mimic a VWF:RCof-like activity has also been recently described (‘SE’), as has the production and characterisation of a large number [n = 10] of locally generated anti-VWF MAB. In the current study, we have adapted these MAB to in-house ELISA assays to assess their utility for VWD diagnosis and subtype discrimination, and to compare them with other assay systems. Thus, the VWF:CBA, VWF:RCof by agglutination, the SE assay, and in-house MAB based assays have been directly compared for their ability to discriminate Type 1 [n = 9] from Type 2 VWD samples [phenotypes 2A and 2B; n = 11]. In summary, MAB-based systems can be used to measure VWF and confirm a diagnosis of VWD, as well as exhibiting some VWD-subtype-discriminatory capabilities. However, better evidence of VWF-discordance was usually achieved using the VWF:RCof (agglutination) assay, while the greatest degree of VWFdiscordance was consistently observed using the VWF:CBA assay. In conclusion, the VWF:CBA assay proved to offer the best diagnostic predictive tool for a Type 2 VWD defect, while MAB-based systems appear to be less effective in this regard.Abbreviations: HMW: High Molecular Weight [VWF], MAB: Monoclonal antibody (/antibodies), PNP: Pooled Normal Plasma, RIPA: Ristocetin induced platelet aggregation, VWD: von Willebrands disease (/disorder), VWF: von Willebrand Factor, VWF:Ag: von Willebrand Factor Antigen (assay), VWF:CBA: Collagen Binding [Activity] Assay for VWF, VWF:RCof: Ristocetin Cofactor Assay for VWF
Keywords: von Willebrand factor; VWF; von Willebrands disease; von Willebrand disorder; VWD; diagnosis; Collagen binding assay; Collagen; VWF:CBA